The relationship between time of swim start and the power of the lower limbs among young swimmers - Wadrzyk, L.; Staszkiewicz, R. (Journal of Kinesiology and Exercise Sciences, 2018)
Aim: Determining the relationship between time of swim start and the power of the lower limbs in boys and girls. Basic procedures: 32 swimmers, aged 15-16 years performed the CMJ (counter-movement jump) and the SJ (squat jump). The following were measured: jump height (H), maximal speed (vMAX) and maximal power as well as the average in absolute (respectively: P and PA) and relative terms (PREL and PAREL). Registration Recording of the start jumps to any style freestyle with the measurement of the time to cover the first 10 m of the distance was were conducted (t10). The following were determined: flight length and time (Lf, tf), height of hip joints at the time of start signal (Hh), angle in of the hip joints at the time of loss of contact with the block (AT) as well as at the time of immerging fingers in the water (AE), and the water attack angle (AA). The significance of differences between averages noted in the groups of boys and girls were evaluated and the correlations between variables were described. Main findings: The boys achieved lower t10 values and higher Lf, Hh and AT levels. In this group of subjects, only Hh negatively correlated with t10 (r=-0.57). Significant differences in the level of all variables noted for the boys and girls during the CMJ and SJ were observed. At the same time, none of the indicators characterizing CMJ were correlated with t10. In the group of boys, significant correlations were noted between t10 and H, vMAX, P, PREL, PA in SJ (-0.51=r=-0.72). Conclusions: There are differences between the boys and girls in performance of the start jump. One of their causes may be the disproportion in the strength of lower limb muscles. In boys, unlike girls, the SJ jump is valuable in testing the power of the lower limbs significantly correlated with the effectiveness of the start jump. The CMJ jump seems to be of low usefulness in predicting the effectiveness of a swim start.